Djelantik’s Aesthetic Study in the Visual Poster “Every Flower Tells a Story” - Haniyah Ashillah Putri; Mukhsin Patriansah; Tria Puspa Selomita; Muhammad Ridwan (Institut Seni Indoensia Surakarta, 2025)
A poster is a visual communication medium that effectively conveys messages through a combination of design elements such as images, colors, and text. The purpose of this study is to examine the effectiveness of the poster titled